Infinite Selectivity of Wet SiO2 Etching in Respect to Al - Gablech, Imrich; Brodský, Jan; Pekárek, Jan; Neužil, Pavel (Micromachines, 2020)
We propose and demonstrate an unconventional method suitable for releasing microelectromechanical systems devices containing an Al layer by wet etching using SiO2 as a sacrificial layer. We used 48% HF solution in combination with 20% oleum to keep the HF solution water-free and thus to prevent attack of the Al layer, achieving an outstanding etch rate of thermally grown SiO2 of ≈1 µm·min-1. We also verified that this etching solution only minimally affected the Al layer, as the chip immersion for ≈9 min increased the Al layer sheet resistance by only ≈7.6%. The proposed etching method was performed in an ordinary fume hood in a polytetrafluorethylene beaker at elevated temperature of ≈70 °C using water bath on a hotplate. It allowed removal of the SiO2 sacrificial layer in the presence of Al without the necessity of handling highly toxic HF gas.
Keywords: microelectromechanical systems (MEMS); selectivity; sacrificial layer; SiO2 etching